FROM THE SACRED TO THE PROFANE: A SOCIOLOGICAL ANALYSIS AGAINST THE CHANGE IN SOCIAL VALUES IN THE LOMBE TRADITION IN THE CONTEMPORARY ERA - Hoiril Sabariman; Rida Helfrida Pasaribu; Khairunnisa; Anik Susanti; Nyimas Nadya Izana (FISIP Universitas Malikussaleh, 2026)
The buffalo racing tradition or local community Kangean-Madura calling the term of lombe, once regarded as a sacred communal ritual symbolizing solidarity, honor, and agrarian identity, has undergone significant sociocultural transformation in the context of modernization and globalization. This study aims to analyze the sociological dimensions of changing social values in the buffalo racing tradition as it shifts from sacred ritual to profane spectacle. Employing a qualitative approach with ethnographic methods, data were collected through participant observation, in-depth interviews, and documentation involving local elders, tradition organizers, and cultural practitioners. The findings indicate that the buffalo racing tradition has increasingly been influenced by economic motives, tourism development, and media exposure, leading to the commodification of cultural values. Nevertheless, the tradition still serves as a medium for maintaining local identity and social cohesion. From a sociological perspective, this transformation illustrates the tension between cultural preservation and adaptation, as local communities negotiate their traditional values within the global cultural order. The study underscores the need for strengthening cultural resilience and critical awareness to ensure the continuity of indigenous traditions amid global change.